IMPACT OF NANOPARTICLES AS A HOMOGENEOUS CATALYST IN IGNITION CHARACTERISTICS OF WASTE PLASTIC OIL - Suyatno Suyatno (ROTOR, 2023)
A novel approach was employed to develop alternative fuels by blending pyro-oil from used plastic with graphene, which acted as a combustion additive. The biofuels were produced through pyrolysis of high-density polyethylene (HDPE). When evaluating the fuel blends, the fuel properties were analyzed and compared to commercially available diesel fuel, while Fourier transform infrared (FTIR) spectrometry was employed to know the fuel character. The findings demonstrate that including graphene as a combustion additive significantly enhances the Fuel's performance. The phenomena suggest that graphene effectively weakens the dispersion forces among the triglyceride molecules. Consequently, the droplet is easier to burn. By incorporating graphene, the alternative fuels droplet exhibits improved ignition properties, offering potential benefits in terms of efficiency and performance. The additive plays a crucial part in modifying the molecular structure of the Fuel, resulting in enhanced reactivity and ignition characteristics. Furthermore, the analysis of physical properties and spectroscopic data provides valuable insights into alternative fuels' molecular composition and behavior.